Multimodality of political digital discourse on Twitter social media - Suharto, Abdul Wachid Bambang (BAHASTRA, 2024)
As a communication tool, social media has linguistic aspects ranging from letters to discourse, so it is important to be researched from a linguistic scientific point of view to find its meaning. This research aims to identify, elaborate, and analyze digital discourse on Twitter social media related to political elements. This research is based on the multimodal meaning related to communication modes in the form of signs such as writing, images, photos, videos, and other forms that have visual meaning in finding meaning in a communication in twitter posts. The method of this research is qualitative descriptive. The research data is in the form of posts on Twitter accounts that contain political elements. The data analysis technique in this study goes through the reduction and classification stage based on the use of communication modes in digital political discourse. Data collection techniques are carried out by documenting, listening, and taking notes. The results of the research are in the form of identification and explanation of how multimodal has meaning and meaning in digital political discourse on Twitter social media and the contribution of semiotic fashion in the form of writings, images, photos, videos, and other forms that have visual meaning in digital political discourse on Twitter social media as relevance regarding the views of the interests of discourse producers, digital discourse makers with certain semiotic modes to realize discourse,  and interests aimed at the creation of political digital discourses such as identity politics, politics of struggle, and power politics.